1999
DOI: 10.1038/sj.bjc.6690702
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake, cytotoxicity and DNA-binding studies of the novel imidazoacridinone antineoplastic agent C1311

Abstract: Summary C1311 is a novel therapeutic agent with potent activity against experimental colorectal cancer that has been selected for entry into clinical trial. The compound has previously been shown to have DNA-binding properties and to inhibit the catalytic activity of topoisomerase II. In this study, cellular uptake and mechanisms by which C1311 interacts with DNA and exerts cytotoxic effects in intact colon carcinoma cells were investigated. The HT29 colon cancer cell line was chosen to follow cellular distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…The results obtained point out that accumulation of C1330 in particular structures is crucial for the effective photokilling of C. albicans cells. In accordance with observations made by others (3,26,29), we observed that the nucleus is not the only structure where C1330 accumulates (30 min at 100 M) (Fig. 6A).…”
Section: Discussionsupporting
confidence: 80%
“…The results obtained point out that accumulation of C1330 in particular structures is crucial for the effective photokilling of C. albicans cells. In accordance with observations made by others (3,26,29), we observed that the nucleus is not the only structure where C1330 accumulates (30 min at 100 M) (Fig. 6A).…”
Section: Discussionsupporting
confidence: 80%
“…Cell cycle perturbations and arrest in G 2 M have been attributed to DNA intercalation and DNA topoismerase II inhibitor activity. 15,[44][45][46][47][48] However, its potency as a selective FLT3 receptor tyrosine kinase inhibitor has been identified only recently. 49 The IC 50 value for HT29 and HCT-116 monolayer cells after 72 h of treatment in our experiments was 1.7 µM and 2.7 µM, respectively, and corresponded to the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used one or both of these cytotoxicity assays and/or the differential dye uptake assay in combination with other assay methods (Edwards and Tolkovsky, 1994;Hardwick et al;Hughes et al, 1996;Burger et al, 1999;Lizard et al, 1999;McGuinness et al, 1999;Sumitomo et al, 1999;DeMeester et al, 1997). However, none have used this specific combination of assays in evaluating apoptosis in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%